Fatty Acid Compositions of Different Equisetum Species - Kokten, Kagan; Özel, Halil Barış; Yazici, Hikmet; Iskil, Rabia; Kaya, Zafer; Özel, Halil Barış (Springer, 2020)
[Abstract not Available]
Keywords: Metal Composition; Seeds; Temperature; Profiles; L.